Sustaining capacity building and evidence-based NCD intervention implementation: Perspectives from the GRIT consortium - Rakhra, Ashlin; Mishra, Shivani; Aifah, Angela; Colvin, Calvin; Gyamfi, Joyce; Ogedegbe, Gbenga; Iwelunmor, Juliet (Frontiers in Health Services, 2022)
Background Implementation science has been primarily focused on adoption of evidence-based interventions, and less so on sustainability, creating a gap in the field. The Global Research on Implementation and Translation Science (GRIT) Consortium is funded by the National Heart Lung and Blood Institute (NHBLI) to support the planning, implementation, and sustainability of Late-Stage Phase 4 Translational Research (T4TR) and capacity building for NCD prevention and control in eight low-and middle-income countries (LMICs). This paper highlights perspectives, including barriers, facilitators, opportunities, and motivators for sustaining capacity building and evidence-based hypertension interventions within LMICs. Methods Guided by the Capacity, Opportunity, Motivation, Behavior (COM-B) Model, this study surveyed GRIT consortium members on the barriers, facilitators, key motivators, and opportunities for sustaining capacity building and evidence-based hypertension interventions in LMICs. Thematic analysis was used to identify themes and patterns across responses. Results Twenty-five consortium members across all eight sites and from various research levels responded to the survey. Overarching themes identifying facilitators, key motivators and opportunities for sustainability included: 1) access to structured and continuous training and mentorship; 2) project integration with existing systems (i.e. political systems and health systems); 3) adaption to the local context of studies (i.e. accounting for policies, resources, and utilizing stakeholder engagement); and 4) development of interventions with decision makers and implementers. Barriers to sustainability included local policies and lack of infrastructure, unreliable access to hypertension medications, and lack of sufficient staff, time, and funding. Conclusion Sustainability is an important implementation outcome to address in public health interventions, particularly as it pertains to the success of these initiatives. This study provides perspectives on the sustainability of NCD interventions with a focus on mitigating their NCD burden in LMICs. Addressing multilevel factors that influence the sustainability of capacity building and interventions will have notable implications for other global NCD efforts going forward. Current and future studies, as well as consortium networks, should account for sustainability barriers outlined as it will strengthen program implementation, and long-term outcomes.